PENGEMBANGAN SUMBER DAYA MANUSIA DAN EFIKASI DIRI PENGARUHNYA TERHADAP KINERJA PEGAWAI DENGAN KEPUASAAN KERJA SEBAGAI VARIABLE INTERVENING - Aza Kamella Gusmenta; Eti Arini (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study aims to determine the Effect of Human Resource Development and Self-Efficacy on Employee Performance with Job Satisfaction as an Intervening Variable (Case Study of the Public Works and Spatial Planning Agency of Mukomuko Regency). This study uses a quantitative approach. The total number of employees of the Public Works and Spatial Planning Agency of Mukomuko Regency is 91 people and all of them are used as samples in this study. There are several tests used in this study, namely Instrument Test (Validity Test and Reliability Test), Classical Assumption Test (Normality, Multicollinearity Test and Heteroscedasticity Test) and using Multiple Regression Analysis, Regression Equation Analysis and Determination Coefficient Analysis (R2) as well as using Hypothesis Test (Perial t-Test and Simultaneous F-Test). The results of this study indicate that Human Resource Development and Self-Efficacy have a significant effect on the Performance of Employees at the Mukomuko Regency Public Works Department, both directly and through Job Satisfaction as an intervening variable. Appropriate HR development improves competence and job satisfaction, while high self-efficacy strengthens employee confidence and work motivation. Job satisfaction has been shown to be an important link that strengthens the influence of both variables on performance, so that the overall findings emphasize the importance of increasing employee capacity, self-confidence, and work well-being to achieve optimal performance. Keywords: Self-Efficacy, Employee, Performance and Job Satisfaction